OVERVIEW OF COASTAL COMMUNITY BEHAVIOR IN DURIAN VILLAGE, MEDANG DERAS DISTRICT, BATU BARA REGENCY IN 2024 - Puspitasari, Inda; Susanti, Nofi; Shindu, Shindu Keysah (HEARTY, 2025)
Coastal communities are a group of people who live together inhabiting coastal areas and then form and have a distinctive culture related to their dependence on the use of coastal resources. The problem of home sanitation, the environment, and the behavior of people in coastal areas is still one of the main problems, as well as in the Durian Village area, Medang Deras District, Batu Bara Regency. The purpose of this study is to find out the description of behavior in communities in coastal areas, especially in Durian Village, Medang Deras District, Batu Bara Regency. The data collection methods used were observation, questionnaires, and conducting in-depth interviews with a sample of 40 respondents. The results obtained from this study are  that clean water sanitation in the community there can be said to be good because the whole community has used their main water and the whole house has used family latrines or private latrines so that no one anymore throws their feces or feces carelessly. However, there are still many people who do not pay attention to their personal hygiene such as lack of awareness that it is important to wash hands before and after eating and/or after defecation. The environment around the village is also far from healthy because there are no facilities that support environmental facilities such as garbage dumps, and there are still many people who throw their garbage into the river and throw their garbage carelessly in their yards.